Building new social contracts: a critical review of ideas and actions to fulfill African aspirations through education - Sweta C. Saxena; Giuseppe Tesoriere; Syed T. Ahmed; Wafa Aidi (National Accounting Review)
This article proposes a theoretical framework for constructing a new social contract through education based on three levers—affordability, accessibility, and applicability—focusing on Africa. The article argues that if governments make education more affordable, accessible, and applicable, they can ensure a virtuous cycle of trust between the government and people, resulting in policies that deliver equal opportunities, create intergenerational mobility, and reduce poverty. The contribution of the framework lies in providing a foundation for new public policy research on the interaction between sector development (like education) and social contract building. The framework is designed to be sufficiently general to systematically investigate broad trends in public policies and sufficiently flexible to accommodate specific micro-contexts in developing countries.